JONATHAN EDWARDS AND THE PARTING OF THE WAYS? - Helm, Paul (Jonathan Edwards studies, 2014)
In an article on the significance of Jonathan Edwards’ determinism, "Jonathan Edwards and the Absence of Free Choice; A Parting of Ways in the Reformed Tradition,"[1] Richard A. Muller has argued that the publication of Edwards’ work on the will signalled a sea-change in the Reformed tradition’s understanding of the nature of human agency. Far from being a champion of confessional Reformed theology on the will, as he has been thought to be in modern times, Muller claims that Edwards was in fact a novel and divisive influence. He proceeds to identify and analyze instances of such division in eighteenth-century England and nineteenth-century Scotland. Interspersed within his account of these divisions he makes various theological claims. He maintains that behind these divisions is one fairly precise claim: that prior to Edwards the Reformed view of human nature was that mankind has the liberty of indifference and not merely the freedom from constraint associated with compatibilist determinism, which Edwards espoused. [1] Richard A. Muller, "Jonathan Edwards and the Absence of Free Choice: A Parting of Ways in the Reformed Tradition," Jonathan Edwards Studies 1, no. 1 (2011).